In Shortage: Understanding Global Antibiotic Supply Chains Through Pharmaceutical Trade Fairs - Zhang, Mingyuan (Anthropologica)

(untitled) (University of Victoria, 2023)
Many countries have reported supply shortages of antibiotics in recent years. The COVID-19 pandemic has sparked interesting discussions among government officials, public health practitioners, and scholars on how to maintain the security of the global pharmaceutical supply chain and how to decrease dependency on countries such as China. This article discusses the experiences and initial findings of tracing global pharmaceutical supply chains through pharmaceutical trade fairs and events at multiple locations. I argue that the reasons behind antibiotic supply shortages are multifold. Although the geographical concentration of the production of key raw materials and Active Pharmaceutical Ingredients (APIs) in China is considered the main reason for the unstable and disrupted supply chain, it is also important to recognize that the same forces that have driven Western pharmaceutical companies to shift some of their less profitable manufacturing lines to China are also challenging Chinese pharmaceutical companies to adjust and reorient their strategies. As such, antibiotics are facing a conundrum in which the governance of excessive use is complicated by a shortage problem that hampers access to essential drugs.